2019
DOI: 10.1021/acsmedchemlett.9b00259
|View full text |Cite
|
Sign up to set email alerts
|

Development of Fluorogenic Substrates of α-l-Fucosidase Useful for Inhibitor Screening and Gene-expression Profiling

Abstract: Inhibitors of human α-l-fucosidases, tissue α-l-fucosidase (tFuc), and plasma α-l-fucosidase reportedly play roles in multiple diseases, suggesting their therapeutic potential for gastric disease associated with Helicobacter pylori and fucosidosis. Terminal fucose linkages on glycoproteins and glycolipids are a natural substrate for both enzymes; however, there are currently no fluorogenic substrates allowing their cellular evaluation. Here, we described the development of novel three-color fluorogenic substra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 27 publications
(53 reference statements)
0
12
0
Order By: Relevance
“…Such a finding is consistent with previous binding studies involving α-fucopyranosides. 45,46 Moreover, QM-NHαfuc proved essentially non-toxic in both control and senescent cells even at concentrations up to 100 μM (Fig. S11 † ).…”
Section: Resultsmentioning
confidence: 97%
“…Such a finding is consistent with previous binding studies involving α-fucopyranosides. 45,46 Moreover, QM-NHαfuc proved essentially non-toxic in both control and senescent cells even at concentrations up to 100 μM (Fig. S11 † ).…”
Section: Resultsmentioning
confidence: 97%
“…Inhibitor Screening The targeted Golgi β-galactosidase activity was previously observed in three human cell lines, HeLa cells, HT-1080 cells, and SK-N-SH cells, using QMC platform-based fluorogenic substrates. 12) To construct the cellbased inhibitor HTS system in a 96-well format to identify inhibitors, we used HeLa cells and our developed fluorogenic substrate 1 incorporating 2-methyl TokyoGreen (2MeTG) as the fluorophore. Substrate 1 has an acetyl modification that provides cell-membrane permeability.…”
Section: Resultsmentioning
confidence: 99%
“…9) Previously, we developed fluorogenic substrates for a β-galactosidase based on the quinone methide cleavage (QMC)-substrate design platform. [10][11][12][13][14] and discovered unreported β-galactosidase activity in the Golgi apparatus in three human cell lines. 12) This newly discovered β-galactosidase activity is entirely different from that of GLB1 isoform 1 and galactocerebrosidase; however, we could not identify the protein responsible for this activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We first observed that, the red fluorescence of To demonstrate the scope of the AIE-based glycocluster for glycosidase sensing at the cellular level, we further used TD-Fuc6 for probing the endogenous AFU activity in 293T (human embryonic kidneys) cells. 68 Cells pre-treated with a known AFU inhibitor (1deoxyfuconojirimycin) 69 were used as control. To our delight, an intensive fluorescence emission corresponding to the residual AIEgen of TD-Fuc6 after removal of the fucosyl epitopes was observed in the cytoplasm of 293T cells (Fig.…”
Section: Fluorescence Imaging Of Glycosidases In Cells With the Hexavalent Glycoclustersmentioning
confidence: 99%